(3GdeNGQL aj GdMjd (B((3YfO CHj MfjaI GdfYeGf(B)s - (3CHh MfjaI , CHh MfjaI,J (B150 (3g` s
(3ChdgG (B:s
(3HGH GdMjd aj GdWdGb s
(3BNQgG (B:s
(3hEdG adG SHjd Ydi GdOGQ hEf GSJMb QLd gPg GdOGQ QLY GdoeTJQj s
(3JcQQ CjVkG JMJ Qbe (B161 (3abg Mfais
(3JHUQI GdYfhGf (B:s
(3QhGjI s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B36 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B104s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdMfajs